Aplikasi Pengukur Kinerja Dosen Berbasis Sistem Inferensi Fuzzy Studi Kasus: Universitas Tanri Abeng - Annisa Dayumi; Arman Arman; Johny Hizkia Siringo (Teknik Informatika, 2018)
Intend to elevate and to maintain the education quality, Tanri Abeng University puts the lecturer performance as one of the important indicator. University has obligation to make sure that the academic process run well. Thus, every stake holder on its circle need to be evaluated and developed periodically. Lecturer’s evaluation is one of them. Currently the evaluation has been done on paper based and manually post processed. This research proposed a fuzzy inference based system to replace the paper based evaluation and manual post processing. The proposed system enable the students to do computerized lecturer’s evaluation. Besides, the fuzzy system inference process will help the management to get more consistence conclusion of the evaluation compared to the manual post processing that potentially lead to the subjectivity.